2001
DOI: 10.1103/physreve.64.021201
|View full text |Cite|
|
Sign up to set email alerts
|

Energy and pressure of shearing fluids at different state points

Abstract: Nonequilibrium molecular dynamics simulations are reported at different strain rates (gamma) and thermodynamic state points for a shearing atomic fluid interacting via a Lennard-Jones potential. Our simulations are performed at the Lennard-Jones triple point, a point midway between the triple point and the critical point, and a high point closer to the critical temperature. We find that, for the mid-point and high point, the energy and hydrostatic pressures have strain-rate dependencies of gamma(2), in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…However, in atom-scale simulations using two-and three-body potentials, the exponent was observed to be ζ ≈ 2.0 away from the triple point [35]. The deviation was ascribed to two-body interactions [36,37]. Further systematic studies using the Lenard-Jones potential found the exponent in the range ζ = 1.2-2.0 as a function of density and temperature [38], thereby rendering ζ = 3/2 only a special case.…”
Section: Pressure Fluctuationsmentioning
confidence: 96%
“…However, in atom-scale simulations using two-and three-body potentials, the exponent was observed to be ζ ≈ 2.0 away from the triple point [35]. The deviation was ascribed to two-body interactions [36,37]. Further systematic studies using the Lenard-Jones potential found the exponent in the range ζ = 1.2-2.0 as a function of density and temperature [38], thereby rendering ζ = 3/2 only a special case.…”
Section: Pressure Fluctuationsmentioning
confidence: 96%
“…The α = 3/2 exponent is consistent with both mode‐coupling theory9 and simulation data at the triple point of the 12‐6 Lennard‐Jones fluid. However, nonequilibrium molecular dynamics (NEMD) simulation data12–14 for the pressure of a fluid under shear away from the triple‐point indicates that the value of α varies continuously from 1.2 to 2 depending both on temperature and density.…”
Section: Introductionmentioning
confidence: 99%
“…After this value, they increase rapidly as the shear rate increases. For simple fluids, NEMD simulations have demonstrated that the pressure or energy as a function of shear rate under planar shear flow follows a power law [15,16]. The results from this study seem unlikely to give such a simple relationship for long chain systems.…”
Section: Simulation Resultsmentioning
confidence: 58%